Financialisation, social provisioning and well-being in five EU countries - Santos, Ana C. (2016)
This paper aims at providing an overall assessment of the relation between financialisation and well-being in five EU countries and thereby contribute to broader theoretical and policy-related discussions. It seeks to contribute to the financialisation literature by examining the differentiated impacts of financialisation on individuals and households. And it does so by analysing four conduits through which financialisation processes have impacted on well-being. First, it assesses the differentiated involvement of individuals and households with financial markets through both their savings and borrowing behaviours, which are not homogenous across the various socioeconomic groups nor across countries. Second, it examines the impact of financialisation through its effects on the housing system of provision, exposing how financialisation interacts with corresponding systems of provision and how such interactions entail new forms and levels of inequality. Third, the impact of financialisation is examined through the broader effects of the financial crisis on employment, disposable income and welfare provision. Finally, the impact of financialisation is examined by taking into account the perspectives of those excluded from financial markets, further exposing the inequalitygenerating effects of financialisation processes. The paper offers a more nuanced account than that presently available in the financialisation literature. While the rise of finance in the more mature capitalist economies has generally occurred in tandem with systemic regressive structural transformations (e.g. sluggish real wage growth, corporate restructuring, weak corporate social responsibility, roll-back of public services, etc.), these changes were not uniformly felt across the household sector and countries.